Congenital rubella and cytomegalovirus infections in and around Chandigarh - Singh Mini; Arora Shamma; Das Anindita; Mishra Baijayantimala; Ratho Radha (Wolters Kluwer Medknow Publications, 2009)
Aims: This study has analyzed the role of rubella and cytomegalovirus (CMV) in infections of children and pregnant women. Settings and Design: The study was carried out in a tertiary care hospital. Data from blood samples from pregnant women (asymptomatic and also women with obstetric problems) and children (suspected of intrauterine infections) that were received in the laboratory over a period of 8 years were analysed. Materials and Methods: The samples were tested for rubella- and CMV-specific IgM antibodies by capture enzyme linked immunosorbent assay. Results: In children, the overall positivity for rubella- and CMV-specific IgM antibodies was 2.8% and 12.5%, respectively. In asymptomatic pregnant females, rubella positivity was 0.7% while in women with obstetric complications it was 3.4%. IgM antibody positivity in cases of CMV was 7.8% in both asymptomatic pregnant women and also in women with obstetric complications. Conclusions: The study indicated that infection with CMV is more common than the rubella virus. The incidence of rubella has reduced over the past few years. Hence, screening for rubella infection may be reserved for women with obstetric complications only. The routine screening for CMV among all antenatal cases is a debatable issue